Binder Influence on Polyantimonic Acid-Based Membranes’ Electrical Behavior for Low-Temperature Fuel Cells - Sofia Mendes; Pedro Faia (Solids)
The development of innovative proton-conducting materials for low-temperature fuel cells (FCs) is, today, a central topic among the scientific community. Polyantimonic acid (PAA) is characterized by high conductivity and sufficient thermal stability; however, PAA-based solid membrane fabrication with high proton conductivity remains challenging. Additionally, PAA cannot be compacted into solid shaped electrolytes without a binder. In a previous work, using a fluoroplastic binder, the authors fabricated and investigated proton conductivity of bulk PAA-based membranes in the temperature range 25–250 °C. In the present research, the authors opted to use another binder, poly(vinyl alcohol), PVA (which already allowed to obtain PAA sensors with higher sensitivity to moisture, low hysteresis, and similar aging than the produced previously with the fluoroplastic binder), for fabricating new solid membranes. The sample’s structure and morphology were studied using diverse experimental techniques (Thermogravimetric analysis, X-ray diffraction analysis, etc.). Electrical Impedance spectroscopy, EIS, was used to assess the electrical response and respective time stability of the membranes; it also allowed the development of an equivalent model circuit to better interpret the samples’ electrical behavior and respective contributions. The samples with 20 wt% PVA content showed improved protonic conductivity and chemical stability up to 100 °C, when compared to previous prepared and reported ones using the fluoroplastic binder.